Maternal height, gestational diabetes mellitus and pregnancy complications. (August 2021) - Chu, Anne H.Y.; Yuan, Wen Lun; Loy, See Ling; Soh, Shu E.; Bernard, Jonathan Y.; Tint, Mya-Thway; Ho-Lim, Sarah S.T.; Goh, Huecin; Ramasamy, Adaikalavan; Kumar, Mukkesh; Goh, Claire; Ang, Li Ting; et al.
Abstract: Aims: To explore the glucose-overload hypothesis of artefactual gestational diabetes (GDM) diagnosis in shorter women during oral glucose tolerance testing (OGTT), by investigating associations between height and maternal glycemia; and GDM and pregnancy complications in height-groups. Methods: Women from GUSTO (n = 1100, 2009–2010) and NUH (n = 4068, 2017–2018) cohorts underwent a mid-gestation two and three time-point 75 g 2-hour OGTT, respectively. GDM-related complications (hypertensive disorders of pregnancy, preterm delivery, emergency cesarean section, neonatal intensive care unit admission, macrosomia, birthweight) were compared within shorter and taller groups, dichotomized by ethnic-specific median height. Results: Using WHO-1999 criteria, 18.8% (GUSTO) to 22.9% (NUH) of women were diagnosed with GDM-1999; and by WHO-2013 criteria, 21.9% (NUH) had GDM-2013. Each 5-cm height increment was inversely associated with GDM-1999 (adjusted odds ratio [aOR, 95% CI] = 0.81 [0.76–0.87], 2-h glycemia (adjusted β [aβ, 95% CI] = -0.171 mmol/L [-0.208, -0.135]) and 1-h glycemia (aβ = -0.160 mmol/L [-0.207, -0.112]). The inverse association between height and 2-h glycemia was most marked in "Other" ethnicities (Eurasians/Caucasians/mixed/other Asians) and Indians, followed by Chinese, then Malays. Compared with non-GDM, GDM-1999 was associated with preterm delivery (aOR = 1.76 [1.19–2.61]) and higher birthweight (aβ = 57.16 g [20.95, 93.38]) only among taller but not shorter women. Conclusions: Only taller women had an increased odds of GDM-related pregnancy complications. An artefactual GDM diagnosis due to glucose-overload among shorter women is plausible.